The contextual factors influencing intuition formation in pediatric nursing settings: A qualitative content analysis - Shilan Azizi; Ali Fakhr-Movahedi; Abbasali Ebrahimian (Kashan University of Medical Sciences, 2023)
Background: Intuition plays an essential role in caring for children with high-risk diseases and making appropriate decisions in critical situations. Understanding the context of intuition will lead to a more appropriate use of intuition.Objectives: This study was proposed to explore pediatric nurses' experiences of contextual factors influencing intuition formation in pediatric nursing.Methods: This qualitative content analysis was conducted on 16 nurses and 2 pediatricians in pediatric settings of Bandar Abbas hospitals, Iran, in 2020. Participants were purposefully selected with maximum variation in job position, age, and work experience. Data were collected through semi-structured interviews that focused on the occurrence of their intuition experiences and influencing factors. The interviews were transcribed and analyzed using the Graneheim and Lundman method of content analysis. To increase the trustworthiness of the data, the codes extracted were peer-checked, member-checked, and external-checked.Results: The theme of "competence in the shadow of limitation and uncertainty" represented the context in which intuition occurred and was used in pediatric nursing. This theme was derived from the two categories "the limited scope and inexplicability of intuitive actions" and "rational mastery."Conclusion: Despite the belief in the role of knowledge and experience in forming intuition, pediatric nurses were mostly reluctant to intervene based on their intuition. Organizational issues such as the limited and ambiguous nature of Iranian nurses' independent practice and the inexplicable nature of intuitive actions have limited pediatric nurses' use of intuition. Hospital leadership should moderate barriers to using intuition by changing mindsets, culture, and legislation.